Distribution of heavy metals in pig farm biogas residues and the safety and feasibility assessment of biogas fertilizer - Jieqiong, Ma; Hongguang, Zhu; Min, Fan (International Journal of Agricultural and Biological Engineering, 2013)
Abstract: The presence of high levels of heavy metals in anaerobic fermentation residues is a major obstacle to the resource utilization and urgent research for removal of heavy metals in the biogas slurry is needed. The handling of large-scale residue slurry and safely returning to field urgently needed constructive suggestion. The contents of heavy metal elements in the residue of anaerobic digestion processes of the wastewater and waste of the piggery were mainly investigated. The contents of heavy metals in the original fluid and the centrifugal solution were determined in this study. They included elements, such as Cu, Zn, Cr, Cd, Pb, As, Ni, Mn, and Se, which were compared with the existing standard including the irrigation water quality standards (GB5084-2005), comprehensive discharge standard of sewage (GB8978-1996) and water-solubility humic acid fertilizer quality standards (NY1106-2010). The preliminary data suggested that both the heavy metals before and after centrifugation were in excess of the standards to some degree and the exceeding standard rate declined ignificantly after centrifugation. The absolute contents of heavy metals after centrifugation declined significantly compared with that before centrifugation. Those ratios are 91.8%, 73.2%, 47.6%, 94.5%, 93.5%, 59.4%, 95.8%, 100% for Zn, As, Cd, Cr, Cu, Ni, Mn,Pb, respectively. A descriptive statistics as well as a correlational analysis showed that there existed strong correlation among Cu, Pb, and the total suspended solids (TS). Meanwhile, significant correlation was found among TS, Cd, Zn, As, Cr, Ni, and Mn at 0.01 level. The data and the analysis above provided the theoretical and experimental support for the removal of heavy mental mainly characterized by the removal of TS. According to the comparison between contents of heavy mental conversed from large amount nutrients and corresponding standard (NY1110-2006), only as was found beyond standard. It was feasible to apply biogas residues after centrifugation as water-solubility fertilizer due to the fact that As had low accumulation efficiency in soil and plants. Keywords: fluid biogas residue, heavy metals, distribution, correlation, fertilization DOI: 10.3965/j.ijabe.20130604.005 Citation: Ma J Q, Zhu H G, Fan M. Distribution of heavy metals in pig farm biogas residues and the safety and feasibility assessment of biogas fertilizer. Int J Agric & Biol Eng, 2013; 6(4): 35－43.